Ecofeminismos y derechos de la naturaleza. Cruces entre ley, Estado y sensibilidades (Papeles, 2021)
In this essay we present a series of reflections focused on the rights of nature (RoN) and ecofeminisms, motivated by the current signs of violence against bodies and territories in Latin America and the Caribbean.We will argue that although they open more than interesting paths of inquiry by disputing what is established by modern laws and institutions, the existing ecocentric and biocentric visions, materialized in the RoN, are traversed by gender inequality. Thus, we promote a more critical view, contemplating that it starts from an unequal and hierarchical position -based on the social construction of gender-, still underlying in the discursive formulation of laws and in the wide range of recognitions it makes. By proposing a synergy between the RoN and ecofeminism, we intend to expand the legal discourse with a theoretical practiceand a sensibility that transcends it.